Complex solutions for Burgers-Like equation - Gençoğlu, Muharrem Tuncay (My University, 2013)
In this paper, a direct algebraic method for the complex solutions of the Burgers-Like was implemented. Several complex solutions of the Burgers-Like were found by using this technique

Bu çalışmada Burgers-Like denkleminin karmaşık çözümleri için doğrudan cebirsel metodu uygulanmıştır. Bu teknik kullanılarak Burgers-Like denkleminin birkaç tane karmaşık çözümü bulunmuştur
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Burgers-Like; Direct algebraic method; Complex solutions; Traveling wave solutions; Doğrudan cebirsel metot; Karmaşık çözümler; Hareket eden dalga çözümleri